The Pleiades Plate Database: a new update - Tsvetkov, M.; Tsvetkova, K.; Borisova, A.; Kalaglarsky, D.; Barbieri, C.; Rampazzi, F.; Kroll, P.; Sergeeva, T.; Sergeev, A.; Mink, D.; Doane, A.; Samus, N. (Кинематика и физика небесных тел, 2005)
New results for the Pleiades Plate Database (PPDB) are presented. The database aims to collect information for the digitized Pleiades plates mainly in the field of 25 square degrees around Alcyone. Using the Wide-Field Plate Database (WFPDB, [http://www.skyarchive.org]) for the Pleiades plate search we found more than 3100 plates existing in the Asiago, Sonneberg, Harvard, Kyiv, and Moscow plate collections. The Pleiades cluster as one of the most observed stellar cluster, which is quite well visible in the Northern sky, is a basic one for many astronomical projects, carried out since the beginning of systematical photographic sky monitoring in 1872 (the Gould survey). More plates from the Asiago, Sonneberg, Harvard, Kyiv, and Moscow wide-field plate archives were scanned and added to the database.